Translation of political discourse: a communicative approach to English translation of his majesty king Mohammed vi’s speeches of 2012 - Ibn Majdoub Hassani, Soukaina (Université sidi mohamed ben abdellah, Faculté des lettres et des sciences humaines-Sais-Fès, 2019)
This dissertation casts light on political translation, particularly the translation of political discourse. With reference to previous research, it was asserted that political speeches should not be altered when translated for they belong to authoritative texts. Other than this, it was argued that it is the function of the source text in the target language community that has to be taken into account when translating a political speech. This dissertation, however, adopted a different perspective. Therefore, it sought to demonstrate the validity of the communicative approach to translation in the political field, particularly when it comes to translating political speeches. To achieve the purpose of the dissertation, three of His Majesty King Mohammed VI’s speeches were selected for translation while applying the principles of the aforementioned approach so as to either confirm its validity or disconfirm it. Most importantly, it was essential to conduct a comparative study between two different translation versions of the same speeches: the previous one provided by the “Moroccan Agency of Press” and my suggested translation. The main objective, in this regard, was to explore the different aspects related to the use of the communicative and the cognitive approaches for the sake of investigating their effectiveness in efficiently and accurately rendering the intended messages of these texts, especially that they are considered to be amongst the most challenging to translate. The study’s findings revealed that the communicative approach is the most valid approach to be adopted by a translator during the translation process of a political speech. Through its use, not only syntactic naturalness was achieved in the target texts, but most importantly, opting for lexical clarity led to a better understanding of these texts’ messages. In contrast to the communicative approach, the use of the cognitive approach proved to be invalid both syntactically and semantically. This is attributed to the fact that, many times, it resulted in syntactic distortion, meaning loss, and led to blocking the communicative function of the target texts through the use of a sophisticated language style.
Keywords: Political translation; Communicative approach; Cognitive approach; Fidelity; Syntactic naturalness; Lexical clarity; Language economy.